Barriers to breastfeeding among mothers in the northern border region of Saudi Arabia: A cross-sectional study - E. Esmaeel, Safya; Khalid Alobaidan, Rahaf; Faez K Alenezi, Dana; Salamah F Alanazi, Farah; Maqil T Alanazi, Rahaf; Dhaher A Alharbi, Atheer; Hameed G Alanezi, Haneen; Hussin A Alruwili, Leen; Abu Alsel, Baraah; A Hamid, Omaima; Hassan Abdalla Hashim, Sawsan; E. Bayomy, Hanaa; Fawzy, Manal S. (Belitung Nursing Journal, 2025)
Background: Although breastfeeding is widely recognized for its essential nutritional and protective health benefits for infants, exclusive breastfeeding rates remain suboptimal in many populations globally and within Saudi Arabia. There is a paucity of region-specific data detailing the barriers to breastfeeding among mothers, particularly in the Northern Border region. Understanding these barriers is crucial for developing culturally appropriate interventions and public health policies that can enhance breastfeeding practices and maternal support systems. Objective: This study aimed to identify and analyze the barriers affecting exclusive breastfeeding among mothers in the Northern Border region of Saudi Arabia. Methods: A community-based cross-sectional survey was conducted among mothers aged 18 years and older residing in the Northern Border region of Saudi Arabia between February and May 2025. Data were collected using a structured, pre-validated online questionnaire in Arabic, disseminated via social media platforms to ensure broad participation. Descriptive statistics were used to summarize participant characteristics and knowledge levels, while inferential statistics were used to examine associations between demographic factors, knowledge scores, and identified barriers. Results: A total of 453 mothers participated in the study (mean age: 36.9 ± 8.1 years), of whom 91.6% reported prior breastfeeding experience. Knowledge scores ranged from 24 to 60 (mean: 46.1 ± 6.9). Higher knowledge levels were observed among mothers aged over 40 years (p = 0.0001), those with more than four children (p = 0.02), and participants with an average standard of living (p = 0.0001). Previous breastfeeding experience was significantly associated with older age (p <0.001) and employment status (p = 0.03). Working mothers, particularly those employed on shifts or hourly wages, reported significantly more barriers to exclusive breastfeeding (p = 0.001, p = 0.03, p = 0.0006). The most frequently reported challenges included insufficient workplace support and inadequate maternity leave, affecting 69.5% of respondents. Conclusion: Barriers to exclusive breastfeeding in the Northern Border region are predominantly workplace-related and institutional, including limited lactation facilities, lack of designated nursing breaks, rigid work schedules, and insufficient organizational support. Addressing these challenges through the implementation of supportive workplace policies, flexible scheduling, and targeted health education initiatives could substantially improve exclusive breastfeeding rates and promote better maternal and infant health outcomes.